Answer is 13.
please explain.
Attachments:
![](https://hi-static.z-dn.net/files/d27/a002049956c687765dac19da26db4d79.jpg)
Answers
Answered by
16
Step-by-step explanation:
let us assume R stands for square root. Then the given expression looks as below.
(R7+R5)
----------- = a+bR35
(R7-R5)
To find the values of a and b, we need to rationalize the denominator R7-R5.
(R7+R5) (R7+R5)
(R7-R5) (R7+R5)
7+5+2R7R5
7-5
12+2R35
2
6+R35 = a+bR35
Hence a=6 and b=1
Answered by
0
Answer:
Step-by-step explanation:
=>√7-√5/√7+√5×√7-√5/√7-√5
=>(√7-√5)^2/(√7)^2-(√5)^2
=>(√7)^2+(√5)^2-2×√7×√5/7-5
=>7+5-2√35/2
=>12-2√35/2
=>2(6-√35)/2
=>6-√35=a+b√35
Then, a=6 and b=-1
(6)^2+4×6×-1+(-1)^2
=>36-24+1
=>37-24=13
Similar questions